Identifying a low‐flow phenotype in heart failure with preserved ejection fraction: a secondary analysis of the RELAX trial. (16th April 2019) - Patel, Kershaw V.; Mauricio, Rina; Grodin, Justin L.; Ayers, Colby; Fonarow, Gregg C.; Berry, Jarett D.; Pandey, Ambarish
Abstract: Aims: The relationship between resting stroke volume (SV) and prognostic markers in heart failure with preserved ejection fraction (HFpEF) is not well established. We evaluated the association of SV index (SVI) at rest with exercise capacity and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) in stable patients with HFpEF. Methods and results: Participants enrolled in the Phosphodiesterase‐5 Inhibition to Improve Clinical Status and Exercise Capacity in Diastolic Heart Failure (RELAX) trial with available data on SVI by the Doppler method were included in this analysis ( n  = 185). A low‐flow state defined by resting SVI < 35 mL/m 2 was present in 37% of study participants. Multivariable adjusted linear regression analysis suggested that higher resting heart rate, higher body weight, prevalent atrial fibrillation, and smaller left ventricular (LV) end‐diastolic dimension were each independently associated with lower SVI. Patients with low‐flow HFpEF had lower systolic blood pressure and smaller LV end‐diastolic dimension. In multivariable adjusted linear regression models, lower SVI was significantly associated with lower peak oxygen consumption (peak VO2 ) and higher NT‐proBNP levels at baseline, and greater decline in peak VO2 at 6 month follow‐up independent of other confounders. Resting LV ejection fraction was not associated with peak VO2 and NT‐proBNP levels. Conclusions: There is heterogeneity in the resting SVI distribution among patients with stable HFpEF, with more than one‐third of patients identified with the low‐flow HFpEF phenotype (SVI < 35 mL/m 2 ). Lower SVI was independently associated with lower peak VO2, higher NT‐proBNP levels, and greater decline in peak VO2 . These findings highlight the potential prognostic utility of SVI assessment in the management of patients with HFpEF.